Studi Perbandingan Jaringan Optik Eksisting dengan Gigabit Passive Optical Network (GPON) di Kampus Universitas Udayana Bukit Jimbaran - I Putu Yuda Pramana Putra; Pande Ketut Sudiarta; Gede Sukadarmika (Jurnal SPEKTRUM, 2018)
The purpose of this study is to compare the existing optical network conditions that use point to point technology with GPON network designed for Udayana University campuses area in Bukit Jimbaran Bali. The Existing optical network is currently able to serve only 14 buildings from 77 existing productive buildings due to the limited number of available optical cores.. It means in order to connect each building at the campuses area, it is required much more optical fiber. Alternatively is using Gigabit Passive Optical Network (GPON) technology. This research was conducted by analyzing the condition of the existing optical network and designing the GPON network. Here are compared some network feasibility parameters ie Link Power Budget, Rise Time Budget and Bit Error Rate. Then compare the use of cores, the number of subscribers as well as device estimation and transmission costs. The study found that to connect all of the buildings are GPON configuration required only 22 optical cores, compared to 154 cores for eksisting network designs. However, the GPON design has lower network quality but is simpler and much more economical if it is implemented for a wide network.